Observational Study: Examining the Meteorological Relationship Between Subarachnoid hemorrhage - Ökkeş Zortuk; Umut Ogün Mutlucan; Cihan Bedel; Fatih Selvi; Cezmi Çağrı Türk (Ķazaķstannyṇ Klinikalyķ Medicinasy)
Background :Subarachnoid hemorrhage (SAH) is a critical condition involving bleeding into the subarachnoid space, commonly presenting with severe headache, nausea, vomiting, dizziness, and loss of consciousness. It is a significant cause of morbidity and mortality, especially in middle-aged and elderly populations, with many deaths occurring within the first 24 hours of hemorrhage onset. Some studies suggest a potential link between SAH and weather conditions, but findings are inconclusive. Aims: This study aims to investigate the relationship between climatic conditions and the incidence of SAH, focusing on variables such as air temperature, dew point, humidity, weather conditions, wind speed, and atmospheric pressure. Methods: A retrospective study was conducted on patients diagnosed with SAH and admitted to a tertiary care hospital's emergency department between January 1, 2023, and December 31, 2023. Inclusion criteria were definitive diagnosis of SAH in patients aged 18 and older and subsequent hospitalization. Weather data at the time of SAH diagnosis were retrospectively reviewed, including daily average air temperature, dew point, humidity, weather conditions, wind speed, atmospheric pressure, and precipitation. Data were analyzed using SPSS 25.0, employing Pearson chi-square and Fisher's exact test for group comparisons. Results: The study included 309 SAH patients. Significant findings include a lower average dew point and higher wind speed and atmospheric pressure on days with SAH admissions. SAH incidence was higher on fair and cloudy days. The lowest SAH prevalence was in June, while the highest was in January. Seasonal analysis showed the highest prevalence in spring and the lowest in autumn. Conclusion: SAH incidence varies by month and season, decreasing in June and autumn. Climatic conditions, particularly dew point, wind speed, and atmospheric pressure, are associated with SAH occurrence. Further research is needed to fully understand the impact of weather on SAH risk.